ENHANCING HUMAN DEVELOPMENT THROUGH EDUCATION: A SWOT ANALYSIS OF EDUCATIONAL POTENTIALS AND CHALLENGES IN KUBU RAYA REGENCY, WEST KALIMANTAN - Farhan, Firda Islamaya (Jurnal Visi Ilmu Pendidikan, 2026)
This study explores the educational potential and challenges in Kubu Raya Regency, West Kalimantan, using a SWOT analysis to identify strategies for improving the Human Development Index (HDI) in the education sector. The research emphasizes the importance of education in Kubu Raya's socio-economic development, focusing on inclusive education, infrastructure accessibility, and teacher competence. While the region has made notable advancements in educational infrastructure and programs, issues such as low average years of schooling, inadequate access to education facilities, and uneven internet distribution persist. The study's findings suggest that collaboration with external parties, strengthening teacher development, and leveraging information and communication technology (ICT) can significantly enhance education outcomes in Kubu Raya. These strategies align with the West Kalimantan Governor Regulation No. 98 of 2022, which provides a framework for accelerating regional HDI improvements. The research concludes by offering policy recommendations to complement sustainable educational development and inclusivity in Kubu Raya Regency.